2018
DOI: 10.1016/j.powtec.2018.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Discrete element simulation of particle motion in ball mills based on similarity

Abstract: This is a repository copy of Discrete element simulation of particle motion in ball mills based on similarity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In DEM, particles can be discrete free bodies [22], or bonded together at contact to form an assembly with arbitrary shapes, which can simulate bulk materials. The latter is called the BPM (bonded particle model) [23].…”
Section: Discrete Element Methodsmentioning
confidence: 99%
“…In DEM, particles can be discrete free bodies [22], or bonded together at contact to form an assembly with arbitrary shapes, which can simulate bulk materials. The latter is called the BPM (bonded particle model) [23].…”
Section: Discrete Element Methodsmentioning
confidence: 99%
“…Contemporary tumbling mills commonly employ protruding elements at the surfaces of operating chambers in order to enhance the circulation and reduce the share of passive part of the fill. Numerical modeling of flow, under the action of lifters, of individual particles of the fill was performed, based on the principle of similarity, in paper [6] by applying the discrete elements method (DEM). Study [7] reported an experimental and numerical comparative analysis of the impact of three different profiles of lifters on power of the mill's drive.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…In the past decades, modeling and numerical simulation have been used to provide a detailed insight and quantitative guidelines for reactor design and optimization. However, existing work for rotary kilns focuses on the flow field [7][8][9], mixing/segregation [10][11][12][13], and heat transfer performance [6,14,15]; simulation of chemical processes in a rotary kiln is still in its infancy due to the complexity of coupling of dense gas-solid flow, heat transfer, and reactions [16]. There are only few modeling researches concerning the reacting flow for rotary kilns, which can be categorized two types.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%